2018
DOI: 10.3389/fpls.2018.00688
|View full text |Cite
|
Sign up to set email alerts
|

Differential Suppression of Nicotiana benthamiana Innate Immune Responses by Transiently Expressed Pseudomonas syringae Type III Effectors

Abstract: The plant pathogen Pseudomonas syringae injects about 30 different virulence proteins, so-called effectors, via a type III secretion system into plant cells to promote disease. Although some of these effectors are known to suppress either pattern-triggered immunity (PTI) or effector-triggered immunity (ETI), the mode of action of most of them remains unknown. Here, we used transient expression in Nicotiana benthamiana, to test the abilities of type III effectors of Pseudomonas syringae pv. tomato (Pto) DC3000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 96 publications
(170 reference statements)
1
23
0
Order By: Relevance
“…In contrast, we previously demonstrated that F. graminearum FgARB93B suppresses ROS induced by both flg22 and chitin (Hao et al, 2019). Similarly, previous reports have shown that some effectors from Pseudomonas syringae differently suppressed ROS induced by flg22 in comparison to chitin, whereas others suppress ROS induced by flg22 and chitin in a similar manner (Gimenez-Ibanez et al, 2018). However, it is unknown how the fungal and bacterial effectors evolve the specificity to suppress ROS triggered by different elicitors.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, we previously demonstrated that F. graminearum FgARB93B suppresses ROS induced by both flg22 and chitin (Hao et al, 2019). Similarly, previous reports have shown that some effectors from Pseudomonas syringae differently suppressed ROS induced by flg22 in comparison to chitin, whereas others suppress ROS induced by flg22 and chitin in a similar manner (Gimenez-Ibanez et al, 2018). However, it is unknown how the fungal and bacterial effectors evolve the specificity to suppress ROS triggered by different elicitors.…”
Section: Discussionmentioning
confidence: 80%
“…Sup-pressor of G2 allele of skp1 (SGT1) is a major stabilizing factor of NLR proteins and is required for T3E-triggered HR (Kadota et al, 2010;Peart et al, 2002). To investigate the SGT1 requirement for RipA1-or RipE1-induced cell death, NbSGT1 expression was knocked-down using VIGS (Choi et al, 2017;Gimenez-Ibanez et al, 2018;Peart et al, 2002). As observed in non-silenced N. benthamiana plants, RipA1 or RipE1 expression triggered cell death in empty vector (EV)-silenced plants ( Fig.…”
Section: Ripe1 Requires Sgt1 To Induce Cell Death In N Benthamianamentioning
confidence: 99%
“…Similar to RipA1, several Pseudomonas syringae T3Es induce cell death independent of NbSGT1 (Choi et al, 2017;Gimenez-Ibanez et al, 2018). Although SGT1 might not be required for every NLR function, it is possible that the cell death observed following expression of these T3Es is not related to their recognition by R protein but rather indicative of a form of cellular toxicity.…”
Section: Ripe1 Requires Sgt1 To Induce Cell Death In N Benthamianamentioning
confidence: 99%
“…Similar comprehensive screenings for bacterial effectors that suppress PTI have been performed in Pto and Xanthomonas euvesicatoria . In Pto, seven out of the 22 effectors tested (32%) can suppress flg22-triggered ROS burst and expression of PTI marker genes in N. benthamiana [33]. In X. euvesicatoria , 17 out of the 33 effectors tested (52%) show the ability to suppress flg22-triggered PTI signaling in N. benthamiana [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, HopX1 from Pto DC3000 (HopX1 Pto ) does not show the protease activity in N. benthamiana [27]. For PTI suppression, HopX1 Pta and HopX1 Pto do not suppress flg22-induced ROS burst and expressions of PTI marker genes in N. benthamiana [33]. X. euvesicatoria possesses two HopX1 family effectors, XopE1 and XopE2 [35].…”
Section: Discussionmentioning
confidence: 99%